PENGARUH STRATEGI PROMOSI DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS PADA BAJU PRELOVED SECOND WOMEN DI KOTA BENGKULU - Setiawati, Eka; Islamuddin, Islamuddin (UM. Bengkulu, 2024)
This study aims to determine what factors influence purchasing decisions, which include: (1) The influence of promotional strategies on purchasing decisions on preloved second women's clothes in Bengkulu City, (2), the influence of Word of Mouth on purchasing decisions on preloved second clothes. Bengkulu City Women. The sample of this study was the Bengkulu City Preloved Second Women's employees, totaling 50 employees by taking all employee populations. Data collection used a questionnaire while data analysis was carried out using multiple regression analysis. The results of the study found that: (1) The influence of the Promotion Strategy has a significant effect on Purchase Decisions on Preloved Second Women's Shirts in Bengkulu City. (2) Word Of Mouth is significant in Purchase Decisions on Preloved Second Women's Clothing in Bengkulu City. (3) The Variable Influence of Promotion Strategy, and Word of Mouth have a significant effect on Purchase Decisions on Preloved Second Women's Shirts in Bengkulu City. Keywords: Promotion Strategy And Word Of Mouth.